Consider that the given series takes the general form,
![a_n=1^{}+10+10^2+10^3+\cdots+10^n](https://img.qammunity.org/2023/formulas/mathematics/high-school/lcppw5tu85qk17ewu162349f29hhdqgotf.png)
Observe that the expression is in geometric progression with first term 1 and common ratio 10, so applying the formula for the sum of geometric progression, the expression becomes,
![\begin{gathered} a_n=(a(r^n-1))/(r-1) \\ a_n=(1(10^n-1))/(10-1) \\ a_n=(1)/(9)\mleft(10^n-1\mright) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/drl2sgixt8hzbzm47zdsxpsub1yl52rusl.png)
Then the 5th term is given by,
![\begin{gathered} a_5=(1)/(9)\mleft(10^5-1\mright) \\ a_5=(1)/(9)(10000^{}0-1) \\ a_5=(1)/(9)(99999) \\ a_5=11111 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/20kkgn66im3f5f8f32bbhuiv08u9y0ngj0.png)
Solve for the 6th term as,
![\begin{gathered} a_6=(1)/(9)\mleft(10^6-1\mright) \\ a_6=(1)/(9)(10000^{}00-1) \\ a_6=(1)/(9)(999999) \\ a_6=111111 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/za4ezncb35r4zx9574sj4c4bql0p9ofndq.png)
Thus, the next two terms are 11111, and 111111 respectively.